(untitled) (Third Sector Social Economic Review, 2021)
The purpose of the study was to determine the relationship between internet usage purposes and social media addiction levels of university students. The research is of the relational screening type and its sample consisted of 439 students from a public university. Data collected through “Purpose of Internet Use Scale(PIUS) and Social Media Addiction Scale - Adult Form(SMAS-AF). According to findings, social media addiction level of one-fourth of the participants were above average. Spending a long time on the internet and social media, social media addiction, gender, academic success are variables that affect internet usage purposes. The ones that use social media excessively, students with low academic success use the internet for a psychological needs, entertainment and socialization purposes. There is a positive significant relationship between psychological needs and socialization dimensions of internet usage purposes and social media addiction. It is concluded that social media addiction increases among the students that use the internet for psychological needs and socialization purposes.